Two modes of DNA double-strand break repair are reciprocally regulated through the fission yeast cell cycle - Ferreira, Miguel Godinho (Genes Dev, 2004)
Several considerations suggest that levels of the two major modes of double-strand break (DSB) repair, homologous recombination (HR), and nonhomologous end joining (NHEJ), are regulated through the cell cycle. However, this idea has not been explicitly tested. In the absence of the telomere-binding protein Taz1, fission yeast undergo lethal telomere fusions via NHEJ. These fusions occur only during periods of nitrogen starvation and fail to accumulate during logarithmic growth, when the majority of cells are in G2. We show that G1 arrest is the specific nitrogen starvation-induced event that promotes NHEJ between taz1(-) telomeres. Furthermore, the general levels of NHEJ and HR are reciprocally regulated through the cell cycle, so that NHEJ is 10-fold higher in early G1 than in other cell cycle stages; the reverse is true for HR. Whereas NHEJ is known to be dispensable for survival of DSBs in cycling cells, we find that it is critical for repair and survival of DSBs arising during G1.